Serodiagnosis Efficacy and Immunogenicity of the Fusion Protein of Mycobacterium tuberculosis Composed of the 10-Kilodalton Culture Filtrate Protein, ESAT-6, and the Extracellular Domain Fragment of PPE68 - Xu, Jia-Nan (American Society for Microbiology, 2012)
In order to identify immunodominant antigens of Mycobacterium tuberculosis that may be used in the serodiagnosis of active tuberculosis (TB), we designed an M. tuberculosis fusion protein consisting of CFP-10 (10-kDa culture filtrate protein), ESAT-6 (6-kDa early secreted antigenic target), and the extracellular domain fragment of PPE68 (PPE68′). Then, the coding sequences of the three proteins were inserted into a prokaryotic expression vector, pET-32a(+). To enhance the immunological response, the proteins were linked together. The fusion proteins with a 6×His tag were successfully overexpressed in Escherichia coli BL21 and purified. The purified proteins were applied for detection of the total IgG titer by using an enzyme-linked immunosorbent assay (ELISA) with human sera from well-characterized TB cases and the control cases, and results were compared to those with purified protein derivative tuberculin (PPD). The ELISA results showed that among 140 cases of confirmed active TB and 70 control cases, CFP-10–ESAT-6–PPE68′ had a sensitivity of 73.3% and specificity of 94.3%, compared to a sensitivity of 66.7% and specificity of 74.3% for PPD and a sensitivity of 65% and specificity of 91.4% for CFP-10–ESAT-6. In addition, the fusion protein CFP-10–ESAT-6–PPE68′ stimulated a higher level of antigen-specific gamma interferon (IFN-γ) release for active-TB patients than PPD and CFP-10–ESAT-6. After immunization of C57BL/6 mice, the findings indicated that the total IgG titers and the concentrations of IFN-γ in mice immunized by CFP-10–ESAT-6–PPE68′ were high and induced strong, long-term humoral immunity compared to results with PPD and CFP-10–ESAT-6. Thus, our study indicates that the fusion protein CFP-10–ESAT-6–PPE68′ may be useful as an immunodominant antigen for the serodiagnosis of active TB.